The Limits of Normalization: Russian-Georgian Relations after the Parliamentary Elections in Georgia - N. Silaev (Международная аналитика, 2016)
The article analyzes the influence of the parliamentary elections in Georgia in October 2016 to Russian-Georgian relations. Ruling party “Georgian Dream” (GD) overwhelmingly won the elections and it shows that the current policy towards Moscow will not be radically revisited. At the same time we can expect GD’s policy will be less flexible, than it was before. So the limits of normalization between Russia and Georgia will be more evident.